(untitled) (Bangladesh Journal of Microbiology, 2016)
Antimicrobial resistance in both pathogenic and commensal bacteria is increasing steadily. Failure of antibiotic resistant bacteria containment is responsible for this expansion. Healthcare effluent acts as the store house of harmful infectious pathogens. Potential health risk includes spreading of diseases by these pathogens and wide dissemination of antimicrobial resistance genes. The present study was carried out to investigate the multiple-drug resistance among the bacterial strains that were isolated and identified from the effluents of Jessore Medical College Hospital & Jessore Queens hospital private limited. Identified bacteria were E. coli , Klebsiella spp., Enterobacter spp., Proteus vulgaris and Salmonella spp.. Occurrence of E. coli and Enterobacter spp. were found to have the highest percentages and present in majority of the samples. The identified organisms antibiotic resistant pattern were analyzed by agar disc diffusion method against 6 antibiotics. Results of antibiotic susceptibility test showed that all of the isolates were multi-drug resistant (e4). From the study, we observed that 75% of the isolates were resistant to amoxicillin, followed by Ampicillin (64%), Chloramphenicol (31%), Gentamycin (29%), Nitrofurantoin (27%) and least resistant being Ciprofloxacin 23%. Among the isolates Salmonella spp. were showed highest rate of resistance against all the used antibiotics. The result denotes that, the identified bacteria have been well exposed to the tested antimicrobials and they have established mechanisms to avoid them. Therefore, proper waste water treatment plant should be established to diminish the risk of disseminating multiple drug resistant microorganisms for the safeguard of public health. Bangladesh J Microbiol, Volume 32, Number 1-2,June-Dec 2015, pp 21-24